2019
DOI: 10.1074/jbc.ra119.010917
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plant ER oxidoreductin 1 (ERO1) activity for efficient oxidative protein folding

Abstract: In the endoplasmic reticulum (ER), ER oxidoreductin 1 (ERO1) catalyzes intramolecular disulfide-bond formation within its substrates in coordination with protein-disulfide isomerase (PDI) and related enzymes. However, the molecular mechanisms that regulate the ERO1-PDI system in plants are unknown. Reduction of the regulatory disulfide bonds of the ERO1 from soybean, GmERO1a, is catalyzed by enzymes in five classes of PDI family proteins. Here, using recombinant proteins, vacuum-ultraviolet circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…It has been reported that ERO1L is transcriptionally regulated by the ER unfolded protein response 25 , 26 . To distinguish this possibility in PDAC, we assessed whether ERO1L expression is induced upon treatment with three established chemical inducers of ER stress: thapsigargin, tunicamycin, and dithiothreitol (DTT).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ERO1L is transcriptionally regulated by the ER unfolded protein response 25 , 26 . To distinguish this possibility in PDAC, we assessed whether ERO1L expression is induced upon treatment with three established chemical inducers of ER stress: thapsigargin, tunicamycin, and dithiothreitol (DTT).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate complex formation between P5 and other PDIs via non-covalent interactions, we used the far-western dot blot method [ 44 , 45 , 55 , 56 ] ( Figure 1 b,c). Briefly, we fixed known concentrations of reduced forms of PDIs as prey proteins onto a nitrocellulose membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Far-western dot blot analyses were performed by optimizing the method reported in previous studies [ 44 , 45 ]. Reduced purified protein solutions (40 µM) were diluted to an appropriate concentration, and a 3 µL aliquot was dotted onto a ClearTrans nitrocellulose membrane (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…The method has been used for the structural analysis of unknown proteins in the native and other states so far ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%